The Sociology of the Professions : SAGE Publications. - Macdonald, Keith M. (SAGE Publications, 1995)
Macdonald guides the reader through the chief sociological approaches to the professions, addressing their strengths and weaknesses. The discussion is illustrated by examples from the professions in Britain, the United States and Europe. The social exclusivity that professions aim for is discussed in relation to social stratification, patriarchy and knowledge.